Clinical and pathomorphological changes in the rabbit retina after an injection of various doses of the cytostatic melphalan - N. F. Bobrova; T. A. Sorochynska; S. A. Tronina; T. V. Romanova; N. I. Molachaniuk; O. Iu. Bratishko; A. V. Shylyk (Ukrainian Society of Ophthalmologists, 2023)
Background: In recent years, there have been individual reports on intracameral chemotherapy (ICC) for aqueous seeding in retinoblastoma. The effect of melphalan on the structures of the ocular anterior segment (including the cornea, iris and anterior lens capsule) is however, still unknown, since no relevant experimental studies have been carried out so far. Purpose: To experimentally assess the changes in the rabbit anterior segment induced by intracameral injection of various concentrations of the alkylating cytostatic melphalan. Material and Methods: Twelve adult Chinchilla rabbits (22 eyes; age, 5-6 months; weight, 2.5-3 kg) were involved in this experimental study and maintained in the vivarium of the Filatov institute in separate cages under standard conditions. Results: After a 5-µg melphalan injection, corneal and iris changes were reversible and the lens was still clear. With an increase in melphalan concentration in injection solution (to 10, 15 and 20 µg) and time point (to 1 month and 3 weeks) after injection, degenerative changes in some epithelial cells of the iris became irreversible, anterior capsular cataract developed, but the cornea and anterior chamber aqueous remained clear. After a single 20-µg intracameral injection of melphalan, there was depigmentation of the iris, posterior synechia and anterior capsular cataract. Conclusion: Clinical and ultrastructural responses of ocular anterior segment tissue to intracameral melphalan injection depended on the injected dose and time point after injection. Most cells of examined tissues showed the capability to restore their ultrastructure following ceasing of the toxic effect of the drug.